Coupled magnetic excitations in single crystal PrBa(2)Cu(3)O(6.2). - Lister, S; Boothroyd, A; Andersen, N; Larsen, B; Zhokhov, A; Christensen, A; Wildes, A (2001)
The dispersion of the low-energy magnetic excitations of the Pr sublattice in PrBa(2)Cu(3)O(6.2) is determined by inelastic neutron scattering measurements on a single crystal. The dispersion, which shows the effect of interactions with the Cu spin waves, is well described by a model of the coupled Cu-Pr magnetic system. This model enables values for the principal exchange constants to be determined. The results suggest that both Pr-Pr and Cu-Pr interactions are important in producing the anomalously high ordering temperature of the Pr sublattice. Measurements of the Cu optic spin wave mode show that the interlayer Cu-Cu exchange is significantly lower than in YBa(2)Cu(3)O(6.2).